Indoleacetate decarboxylase is a glycyl radical enzyme catalysing the formation of malodorant skatole. Issue 1 (December 2018) - Liu, Dazhi; Wei, Yifeng; Liu, Xuyang; Zhou, Yan; Jiang, Li; Yin, Jinyu; Wang, Feifei; Hu, Yiling; Nanjaraj Urs, Ankanahalli; Liu, Yanhong; Ang, Ee; Zhao, Suwen; et al.
Abstract Skatole is a malodorous compound that contributes to the characteristic smell of animal faeces. Although skatole has long been known to originate from bacterial tryptophan fermentation, the enzyme catalysing its formation has so far remained elusive. Here we report the use of comparative genomics for the discovery of indoleacetate decarboxylase, an O2 -sensitive glycyl radical enzyme catalysing the decarboxylation of indoleacetate to form skatole as the terminal step of tryptophan fermentation in certain anaerobic bacteria. We describe its biochemical characterization and compare it to other glycyl radical decarboxylases. Indoleacetate decarboxylase may serve as a genetic marker for the identification of skatole-producing environmental and human-associated bacteria, with impacts on human health and the livestock industry. Skatole is a bacterial metabolite responsible for boar taint and the objectionable smell of manure. Here, the authors elucidate the final step of skatole biosynthesis, describing the discovery and biochemical characterization of the enzyme catalysing the conversion of indoleacetate into skatole.